Fostering Religious Activities for the Elderly at Harapan Kita Elderly Social Institution Palembang - Ikhsan Sunaryo; Maimunah; Mukmin (Arkus, 2022)
The existence of human civilization cannot be separated from religion because religion is a guide in life and becomes a benchmark that regulates behavior in everyday life. With religion, a person will be able to build character and morals in living life. Because in religion there are rules and guidelines so that humans can carry out activities, behavior, and can return to God in a state of faith. Religion is a nature that develops naturally and some develop according to the will of Allah SWT. The declining physical condition makes the absorption of the elderly in receiving material in the process of religious activities also decrease. This is marked by a decrease in the sense of sight, sense of hearing, and memory of theelderly. The declining physical condition of the elderly will greatly affect the implementation of Islamic religious education activities that they follow. This factor is a natural factor that is usually experienced by the elderly, it cannot be changed because it is a destiny that must be lived. The inhibiting factors encountered in religious development at the orphanage were monotonous delivery of material, declining physical condition of the elderly, and communication barriers.